Efektifitas Ekstrak Tanaman Meniran (Phyllanthus niruri) Sebagai Antibakteri Edwardsiella tarda Secara In Vitro [Effectivity Of Meniran (Phyllanthus niruri) Extract as Edwardsiella tarda Antibacterial According In Vitro] - Sudarno Sudarno; Fabi Aisah Setiorini; Hari Suprapto (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
AbstractMedicinal plants proven to effectively cope with bacterial diseases one of which is the plant meniran (Phyllanthus niruri). Phyllanthus niruri can act as an antibacterial because it has an antibacterial ingredient content of flavonoids, alkaloids, phenols, and tannins. This shows that plants can be used as an antibacterial Phyllanthus niruri of E.tarda. The purpose of this study was to determine the ability of the antibacterial of Phyllanthus niruri extracts and to find out the best concentration of Phyllanthus niruri extracts as antibacterial E.tarda according in vitro. The experiment was conducted in January 2011, housed at the Laboratory of Bacteriology Juanda Fish Quarantine Center and Laboratory of Organic Chemistry and Technology Faculty of Airlangga University Saints. This research method is done by the Minimum Inhibitor Concentration (MIC) and Minimum Bacterial Concentration (MBC) with 12 treatment. The results showed that the best concentration for the treatment of the concentration of 0.0313 g / ml as indicated with no growth of bacteria and is the lowest concentration of the dilution.